Odpowiedź :
Odpowiedź:
1,
x^2+6x-4x-24=x^2-4x
6x-24=0
6x=24/:6
x=4
2.
x^2-x+4x-4=x^2+2x+9-1
-x+4x-4=2x+9-1
3x-4=2x+8
3x-2x=8+4
x=12
3.
2x-2+3x=4-2+2x
3x=4
x=4/3
x=1 1/3
4.
6x-6-4=-24+6x+14
6x-6x=-24+14+4+6
0=0
Szczegółowe wyjaśnienie:
liczę na naj :p
Odpowiedź:
1. (x-4)(x+6)=x(x-4)
x^2+6x - 4x - 24=x^2 - 4x
x^2 - x^2 - 4x+6x+4x=24
6x=24 /:6
x=4
2. (x+4)(x-1)=x(x+2)+9-1
x^2 - x+4x - 4=x^2+2x+9 - 1
x^2 - x^2 - x+4x - 2x=9 - 1+4
x=12
3.2(x-1)+3x=4-(2-2x)
2x - 2+3x=4 - 2+2x
2x+3x - 2x=4 - 2+2
3x=4 /:3
x=4/3
Szczegółowe wyjaśnienie: